BERBAGAI FAKTOR DISINTEGRASI SUDAN SELATAN TAHUN 2011 - Nova Nurlia (HI 15 UMY 215, 2015)
*215 Political dynamics of countries of Africa and the Middle East-indeed an interesting issue to be discussed. One of them is the events of the disintegration of Sudan's North and South Sudan in 2011. The existence of the southern Sudanand Sudan apparently has some differences, both on the field of political-economic, social or governance. both these regions each have pros and cons that can actually complement each other, but the result of a feud which failed toresolved then both regions experienced dis-integration. To answering the question about the process on sintegrasi between the Sudan and the southern Sudan in 2011 national integration theory on nationalintegration is a prinsipmnya element in order to carry out the nation's life, including social, cultural economics,then in essence emphasizes national unityintegration of perception and behavior among groups in society. This study uses qualitative methods, i.e., methods of research that focuses on the analysis of data which is non-numeric and without using statistical formulas ashis approach. While its data collection techniques are done through the researchlibrary (library research), through this research can be proved that the success ofSouth Sudan on independence in 2011 turned out to not be separated fromreligion, the economic factors related to the pattern of North Sudan's leadershiptends to be diskrminatif and otoritarian, as well as the presence of foreignintervention.